Effect of sulfur concentration on structural, optical and electrical properties of Cu2FeSnS4 thin films for solar cells and photocatalysis applications - Nefzi, Chayma; Souli, Mehdi; Cuminal, Yvan; Kamoun-Turki, Najoua (Superlattices and microstructures, 2018)
Quaternary chalcogenide Cu2FeSnS4 (CFTS) thin films were successfully elaborated by spray pyrolysis technique on glass substrates using different thiourea concentrations (4, 5, 6 and 7.10−2M) as sulfur source. The chemical composition, morphological, structural, optical and electrical properties were investigated using respectively dispersive X-ray spectrometry (EDX), scanning electron microscopy (SEM), X-ray diffraction (XRD), Raman spectroscopy, spectrophotometer and Hall Effect measurements. XRD and Raman spectroscopy revealed that CFTS thin films synthesized at thiourea concentration [S] = 6.10−2M grows with a pure and good crystalline quality. CFTS thin layer crystallized into the stannite structure with the preferred orientation (112) plan. The average grain size reaches a maximum value about 41 nm at [S] = 6.10−2M. The obtained CFTS stoichiometric ratio was Cu:Fe:Sn:S = 2,25/1/0,91/4,08 which is close to the theoretical ratio 2:1:1:4. Optical properties present a high absorption coefficient value equal to 8 104 cm−1, with an estimated band gap value 1,05 eV. This work demonstrates also that electrical resistivity was about 0,46 Ω cm at room temperature and has been decreased to a minimum value of 0,014 at 80 °C. All these experimental results make sprayed CFTS thin film synthesized at [S] = 6.10−2 M as a promising absorber layers in solar devices. Methylene Blue dye under sun illumination has been used to test to photocatalytic activity of optimum CFTS thin film. A value of photo-degradation near 76% of MB dye has been obtained for 4 h duration. This result show that CFTS thin film synthesized at [S] = 6.10−2 M is a good candidate for photocatalysis applications. [Display omitted] •Quaternary chalcogenide Cu2FeSnS4 (CFTS) thin films were elaborated by Spray pyrolysis technique. using different thiourea concentrations (4, 5, 6 and 7.10−2M) on glass substrates.•The band gap energy has been calculated using two different methods it is equal to 1,05 eV.•Optical properties present a high absorption coefficient value equal to 8 104 cm−1.•Electrical resistivity was about 0,46 Ω cm at room.•CFTS thin film elaborated at the optimum thiourea concentration [S] = 6.10−2M can be used as Photocatalytic material which the photo-degradation of MB dye near 76% has been obtained for 4 h duration.